Factors That Affect the Quality of Specialist Services on Patient Satisfaction in the Working Area of Puskesmas Labuhan Haji - Indra Sahputra; Ismail EfendyEfendy; Ramadhani Syafitri Nasution (PROMOTOR, 2024)
Community Health Centers (Puskesmas) have a primary role in providing first-level health services with a focus on promotive and preventive efforts. The main goal is to achieve optimal levels of public health by establishing health regulations. Patient satisfaction is an important focus in assessing the quality of health services. However, there are challenges such as the transfer of participants to other health facilities outside the Community Health Center which can affect services there. This study aims to explore the factors that influence the quality of specialist services and their impact on patient satisfaction at the Labuhan Haji Community Health Center in 2023.